2020
DOI: 10.3389/fpsyg.2020.00863
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Working Memory and Probability Format on Bayesian Reasoning

Abstract: Bayesian reasoning is common and critical in everyday life while the performance on Bayesian reasoning is rather poor. Previous studies showed that people could enhance their performance by applying cognitive resources under the natural frequency format condition. Working memory is one of the crucial cognitive resources in the reasoning process. However, the role of working memory on Bayesian reasoning remains unclear. In our study, we verified the effect of working memory on Bayesian reasoning by evaluating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Indeed, there are several precedents for looking at working memory as an underlying factor in reasoning and judgments under uncertainty (e.g., Capon, Handley, & Dennis, 2003;Copeland & Radvansky, 2004). Shi et al (2006) and Yin et al (2020) have in fact specifically found that working-memory ability predicts Bayesian reasoning performance, based on this NSA view interpretation. Experiment 3 uses a reading span test of working memory that is both performance-based and completely without numbers or mathematical calculations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, there are several precedents for looking at working memory as an underlying factor in reasoning and judgments under uncertainty (e.g., Capon, Handley, & Dennis, 2003;Copeland & Radvansky, 2004). Shi et al (2006) and Yin et al (2020) have in fact specifically found that working-memory ability predicts Bayesian reasoning performance, based on this NSA view interpretation. Experiment 3 uses a reading span test of working memory that is both performance-based and completely without numbers or mathematical calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Yet another version of the NSA view (e.g., Sirota et al, 2014;Yin et al, 2020) is that ability to understand and reason about nested sets is a reflection of general cognitive processing ability. If one takes this view, then individual differences in general cognitive processing ability (separately measured) should dominate in accounting for variations in Bayesian reasoning performance.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there are findings about the influence of working memory in Bayesian reasoning: Brase and Hill (2015) 45 stated that there should be no influence. However, Yin et al (2020) 46 found that the interaction between working memory and probability format was significant. Therefore, it would be interesting to implement cognitive load tasks additionally in future work.…”
Section: Limitations and Outlookmentioning
confidence: 98%
“…It is considered to be a complex but limited-capacity workspace that temporarily stores and processes information during cognitive tasks ( Baddeley, 1992 , 2001 ). As an important part of cognitive function, working memory plays an important role in learning, reasoning, problem-solving, and intellectual activities ( Sumowski et al, 2010 ; Shipstead and Yonehiro, 2016 ; Chuderski and Jastrzębski, 2018 ; Yin et al, 2020 ; Yoo and Collins, 2022 ). Therefore, clarifying the relationship between the vagal nerve and working memory is of great significance.…”
Section: Introductionmentioning
confidence: 99%